PRESTIGIUL PERSONALITĂȚII – VALOARE FUNDAMENTALĂ A OMENIRII ÎNTR-UN STAT DEMOCRATIC (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
The prestige of the personality – fundamental value of humanity in a democratic stateThe rule of law is one of the most discussed concepts of constitutional law and is indisputably related to the transition from state law to the rule of law. In the literature, contradictory opinions have sometimes been stated, according to which the rule of law corresponds to anthropological needs or that it is a myth, a postulate and an axiom, and on the other hand, the rule of law is a pleonasm, a legal nonsense. The concept of the rule of law is a constitutional reality whose foundation is found in the mechanisms of state power, in the relationship between power and freedom of each individual in society and in the application of the principle of legality in state activity, but also in the behavior of each member of society.